Perancangan Animasi Kesenian “Besutan” Sebagai Penguatan Pendidikan Karakter Bagi Pelajar Jenjang Sekolah Menengah Pertama - Izah, Farah Nur; Widyasari, Widyasari; Arifianto, Pungky Febri (Jurnal Ilmiah Wahana Pendidikan, 2024)
social life and storyline can keep up with the times. In Besutan Art, there are 4 figures with their own characters, namely Besut (protagonist), Rusmini (protagonist), Man Gondho (tritagonist), and Sumo Gambar (antagonist). The characters in Besutan's art become a medium for conveying character values ​​through animation with quantitative descriptive methods using interviews, observations and questionnaires. Researchers also revealed that there was a decline in character in junior high school students, this was based on the results of an interview with Mrs. Merien as a teacher at SMPN 3 Kabuh. The choice of Besutan Art as a medium for Strengthening Character Education for Junior High School students was based on the storyline of Besutan Art which follows current developments. and each character has its own character. However, with the development of the times, the audience's interest in Besutan Art has decreased, so animation has been chosen as a medium of delivery in terms of Strengthening Character Education. This is also supported by the results of questionnaire analysis which shows that 90% of the 70 respondents were interested in making Besutan's art an animation to strengthen character education.